Contemporary gene flow, mating system, and spatial genetic structure in a Jequitibá-rosa (Cariniana legalis Mart. Kuntze) fragmented population by microsatellite markers - Tambarussi, Evandro Vagner (2014)
Cariniana legalis Mart. O. Kuntze (Lecidiaceae) is the largest tree of the Atlantic Forest. To contribute to in situ and ex situ genetic conservation programs for the species, herein we investigate the genetic diversity, inbreeding, intrapopulation spatial genetic structure (SGS), mating system and contemporary pollen flow in three fragmented populations of this species. We found 65 adult trees in the Ibicatu population, 22 in MGI, and four in MGII. Seeds were hierarchically sampled among and within fruits directly from the canopy of 15 seed-trees in Ibicatu (n= 40), five seed-trees in MGI (n= 50), and two seed-trees in MGII (n= 100). Thirteen specific microsatellite loci were developed and validated for 51 C. legalis trees. Eleven loci were polymorphic, revealing a maximum of two to 15 alleles per locus. Using the progeny arrays and seed-tree genotypes, we investigated the Mendelian inheritance, genetic linkage and genotypic disequilibrium of seven microsatellite loci specifically isolated for C. legalis and two previously developed heterologous microsatellite loci. No notable deviations from the expected Mendelian segregation, linkage, or genotypic disequilibrium were detected. The average allelic richness in the adult cohort of Ibicatu was 11.65 and 14.29 for MGI-II and for seeds it was 14.18 in Ibicatu and 10.85 in MGI-II; the average observed heterozygosity for adults of Ibicatu was 0.811 and 0.838 for MGI-II and for seeds it was 0.793 in Ibicatu and 0.786 in MGI-II; the average expected heterozygosity for adults of Ibicatu was 0.860 and 0.900 for MGI-II and for seeds it was 0.856 in Ibicatu and 0.853 in MGI-II. The average fixation index was significantly greater than zero for adults and seeds from both populations. Multilocus outcrossing rate ( m t ) in the three populations was significantly lower than unity (1.0), especially in MGII ( m t = 0.830). The rate of mating among relatives was significant when compared to zero only for Ibicatu ( ????0.266) m s t t . Paternity correlation is substantially higher within than among fruits. The average coancestry coefficient ( ??) was higher and variance effective size ( e N ) was lower than expected for halfsib progenies in all three populations. The number of seed-trees necessary for seed collection to obtain progeny arrays with an effective size of 150 was estimated between 54 to 58 seedtrees. The pollen immigration rate was low, especially for the small stands (maximum of 0.4% for MGI), indicating significant genetic isolation of MGI and MGII. The effective pollination radius was also low in MGI (68 m) and MGII (191 m). For MGII, we also found higher levels of selfing (18%) than for Ibicatu (6%) and MGI (6.4%). The substantial genetic isolation of these stands suggest that we can expect an increase in SGS in the future and strategies to increase gene flow and effective population size, such as transplanting individuals among the populations, are desirable for long term in situ conservation. In conclusion, this study produced valuable information for the management of fragmented populations of C. legalis, contributing to breeding programs and providing guidelines for seed collection aimed at conservation and reforestation programs.